The chromatin-binding protein PHF6 functions as an E3 ubiquitin ligase of H2BK120 via H2BK12Ac recognition for activation of trophectodermal genes - Oh, Sungryong; Boo, Kyungjin; Kim, Jaebeom; Baek, Seon Ah; Jeon, Yoon; You, Junghyun; Lee, Ho; Choi, Hee Jung; Park, Daechan; Lee, Ji Min; Baek, Sung Hee (Nucleic Acids Research, 2020)
Epigenetic regulation is important for establishing lineage-specific gene expression during early development. Although signaling pathways have been well-studied for regulation of trophectoderm reprogramming, epigenetic regulation of trophectodermal genes with histone modification dynamics have been poorly understood. Here, we identify that plant homeodomain finger protein 6 (PHF6) is a key epigenetic regulator for activation of trophectodermal genes using RNA-sequencing and ChIP assays. PHF6 acts as an E3 ubiquitin ligase for ubiquitination of H2BK120 (H2BK120ub) via its extended plant homeodomain 1 (PHD1), while the extended PHD2 of PHF6 recognizes acetylation of H2BK12 (H2BK12Ac). Intriguingly, the recognition of H2BK12Ac by PHF6 is important for exerting its E3 ubiquitin ligase activity for H2BK120ub. Together, our data provide evidence that PHF6 is crucial for epigenetic regulation of trophectodermal gene expression by linking H2BK12Ac to H2BK120ub modification.
Keywords: Acetylation; Animals; Cellular Reprogramming; Chromatin; Histones; Homeodomain Proteins; Humans; Mice; Mouse Embryonic Stem Cells; Protein Binding; Protein Processing, Post-Translational; Repressor Proteins; Ubiquitin-Protein Ligases; Ubiquitination